HERMENEUTIKA AL-QUR’AN FAZLUR RAHMAN METODE TAFSIR DOUBLE MOVEMENT - Rifki Ahda Sumantri (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2013)
AbstractThis paper will describe the method of assessment of Al-Quran usingDouble Movement Interpretation. A new approach that emphasizes on awarenessof the text, context, and contextualization. The historical characteristic of Al-Qur'an led to the emergence of the idea and theory of hermeneutic (method ofinterpretation). This theory became work-effort which is so urgent to bedeveloped in understanding the meaning of Al-Qur'an as a whole. It is hoped thatthe theological and legal ethics parts can be placed in a whole (total) coherent.Fazlur Rahman criticized that the classical interpretation methods tend touse the approach in interpreting Al-Qur'an separately, resulting the emergences ofnew problems. The interpreters have implemented the appropriate interpretationof the verse-by-verse chronology in the codex, although sometimes they also referto other verses.Fazlurrahman assumed that the relationship pattern or model of therevelation built between Al-Qur'an (The Text), God (Allah) is the author, andMuhammad ( The Reader and The Author). The assumptions that Muhammad isthe receiver and speaker asserted that Muhammad participated in psychology,both in mental and intellectual in acceptance that revelation